PERFORMANCE EVALUATION OF THREE KINDS OF EXPLOSIVE (ANFO, HEAVY ANFO, AND TITAN BLACK) AT PT PAMAPERSADA NUSANTARA BENDILI SITE - A.J. Sitorus (NIM 12102073), Lesbon
ABSTRACT: Blasting practices at Pama Bendili pit uses three types of explosive: ANFO, Heavy ANFO, and Titan Black. Based on field measurements fragmentation produced by rock blasting using those explosives were dominated by sizes less then 20 cm. i.e., 54.3percent, 56.8percent, and 61.7percent for ANFO, Heavy ANFO, and Titan Black respectively. Meanwhile, prediction using Kuz Ram method, the fragmentation dominated by sizes less then 20 cm i.e., 37.4percent, 38.9percent, 38.5percent for ANFO, for Heavy ANFO, and for Titan Black respectively. By Comparing the difference of fragmentation between field measurement and Kuz Ram fragmentation prediction, correction factors are obtained and these being 0.36 and 0.46 for ANFO, and Heavy ANFO, and Titan Black respectively.